Baseball Pitchers who Suffer Latissimus Dorsi and Teres Major Tendon Injuries Have a High Return to Play Rate After Either Operative or Nonoperative Treatment - Andrew J. Recker, M.D; Max D. Gehrman, M.D; Connor Diaz, B.S; Garrett S. Bullock, D.P.T., D.Phil; Nicholas A. Trasolini, M.D; Brian R. Waterman, M.D (Elsevier, 2023)
Purpose: To provide a concise overview of the prevalence, diagnostic workup, management options, surgical techniques, and reported outcomes in the treatment of latissimus dorsi (LD) and teres major (TM) injuries in professional baseball pitchers. Methods: A systematic review of studies reporting on professional baseball players who sustained LD or TM injuries was performed. Data were collected including patient presentation, injury management strategies, return-to-play (RTP) rates, time to RTP, patient-reported outcome measures, player performance after RTP, preinjury factors associated with injury, and complications. Results: Nine studies with 159 professional baseball players with a LD or TM injury were identified. All studies (2 retrospective cohort studies with high risk of bias and 7 case series) reported shoulder pain after pitching, and magnetic resonance imaging was performed in all cases to confirm diagnosis. Twenty-three patients underwent surgical treatment, whereas 136 patients underwent nonsurgical treatment. Overall RTP rates and performance between surgical and nonsurgical groups were similar (75% to 100% vs 75% to 93%), although the largest study reported improved performance with surgery. Two studies described a surgical technique with a posterior axillary approach and endosteal button fixation of the LD tendon. All studies reported a progressive strengthening and throwing program prior to returning to sport. Conclusion: Professional baseball players who suffer a LD or TM injury have predictable clinical presentations and imaging findings. There is a high RTP rate and performance with both surgical and nonsurgical management. The heterogeneity and low level of evidence of available literature precludes comparative conclusions between treatment approaches. Level of Evidence: IV systematic review of Level III and IV studies.